ХАЛЫҚҚА ХЫЗМЕТ КӨРСЕТИЎ ТАРАЎЛАРЫ ЭКОНОМИКАСЫНЫҢ ГЕОГРАФИЯ ИЛИМИНДЕ ТУТҚАН ОРНЫ - Узақбаев, Қ.К. (FAN va JAMIYAT, 2019)
In the global economy, the service sector networks or the third sector is the most advanced. In the article, from a geographical point of view, service sector networks are evaluated.